SOLUTION OF DIFFERENTIAL EQUATIONS OF INTERACTION BETWEEN CONICAL-HELICAL AGITATOR WITH MINERAL FERTILIZER - S. Nukeshev (Наука и техника)
It has been established that existing mineral fertilizer spreaders do not fully meet technical requirements. In order to ensure continuous and reliable fertilizer dosing it is necessary to destruct bridges above exhaust ports and facilitate forced fertilizer feed to the spreader.The results of theoretical investigations on conical-helical agitator-bridge breaking cone of mineral fertilizers have made it possible to establish interdependence of the motion path of an elementary volume of mineral fertilizers along helical spiral coil of the agitator and its relative speed on functional and technological parameters such as cone-generating angle to its axis,  an angle of lead, a radius of helical surface, coefficients of external and internal friction and an angular velocity. Modifying the above-mentioned parameters it is possible to select the optimum combinations depending on the accepted criteria for  efficient turning.